JUAL BELI THRIFT ONLINE DI KALANGAN GENERASI MUDA : PANDANGAN ISLAM - Irawan, Hengki (Journal Tafkirul Iqtishodiyyah, 2024)
Buying and selling used goods online is permitted in Islam as long as you adhere to the principles and rules of buying and selling. This research uses a qualitative descriptive method in data collection which involves searching for references using library materials. If a law in Islam conflicts with government law, then the law is considered haram, in accordance with government restrictions prohibiting savings on illegally supplied imports. However, when used products have been used by someone whose health is unknown and may or may not be experiencing a serious illness, there will definitely be a lot of bacteria or viruses on the clothes. Therefore, it is best to clean it thoroughly before use. Used goods are no longer associated with poor quality, thanks to the increasing popularity of buying and selling used goods online among young people. Therefore, thrifting is more than just a hobby it is an art form, with shoppers taking pride in their choice of quality branded goods. Apart from that, the frugal culture also has an impact on company growth, especially in the fashion industry in Indonesia.